Self-organization in the 3:2:1 defense in handball: Behaviors from the complex dynamic systems - Espoz-Lazo, Sebastián; Farías-Valenzuela, Claudio; del Val-Martín, Pablo; Hinojosa-Torres, Claudio (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to describe collective emerging behaviors within a 3:2:1 defense training method in handball using the framework of complex dynamic systems. An observational methodology grounded in nonlinear pedagogy was employed, applying constraints to trigger defensive behaviors in response to offensive actions. Twelve players were divided into three groups for participation. The results revealed that emergent defensive behaviors were related to executed offensive actions during the exercise. Offensive ball-circulation actions consistently activated defensive responses aimed at maintaining the defensive structure, while offensive actions involving width and depth crosses prompted position changes, adjustments, and defensive contacts. Furthermore, spontaneous coordination among players was observed to self-organize and adapt defensive responses during the exercise. In conclusion, the nonlinear pedagogy approach rooted in complex dynamic systems was effective in fostering defensive responses in the 3:2:1 defensive system in handball.